Systematic Literature Review (SLR): The Effectiveness of the ICARE Learning Model on Students’ Mathematical Critical Thinking Skills - Chania Salsabila Panjaitan; Heni Pujiastuti; Yani Setiani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The low level of students’ mathematical critical thinking skills remains a significant challenge in 21st-century mathematics education. This condition highlights the need for instructional models that actively engage students in processes of analysis, evaluation, and reflection. One instructional model considered to have the potential to foster these skills is the ICARE model (Introduction, Connection, Application, Reflection, and Extension). This study aimed to review and synthesize research findings regarding the effectiveness of the ICARE learning model in improving students’ mathematical critical thinking skills. The study employed a Systematic Literature Review (SLR) approach based on the PRISMA guidelines. Articles were identified through the Google Scholar database using the Publish or Perish application with the keywords (“ICARE”) AND (“Critical Thinking”) AND (“matematika”). The final search was conducted in May 2026 and covered publications from 2016 to 2026. The articles were screened according to inclusion and exclusion criteria, including document type, topic relevance, full-text availability, research participants, and the alignment of research variables. Of the 376 articles initially identified, 10 studies met the eligibility criteria and were included in the review. Data were analyzed through coding, categorization, comparison, and synthesis of the research findings. The results indicate that most studies reported positive effects of the ICARE learning model on students’ mathematical critical thinking skills. Improvements were consistently observed in students’ abilities to analyze, interpret, evaluate, infer, and draw conclusions. Furthermore, the effectiveness of ICARE was supported by learning activities that promote active participation, reflection, and contextual understanding. These findings suggest that the ICARE model has considerable potential as an alternative instructional approach in mathematics education to enhance students’ mathematical critical thinking skills.